Ironi, humor og opgøret med Hegel i Efterskriften - Henriksen, Mads Gram (Dansk Teologisk Tidsskrift, 2010)
During the last decades, literary studies have shed a long awaited light on the complexities and specificities of Kierkegaard’s writing style. Possibly due to their focus on his so-called aesthetic works, they have left the impression that his style generally is motivated by aesthetic reasons. Contrary to this impression, I argue that Kierkegaard’s style is intrinsically related to the overall project in his authorship, i.e. to become a Christian. In the Postscript, Climacus’ account of what it means to become a Christian is presented largely as a criticism of Hegel’s philosophy and Hegelian theology. In the article, I explore the significance of style for Climacus’ account and I discuss the difference between irony and humour as forms of communication and their inherent limitations. Furthermore, I argue for a connection between irony and humour in the Postscript and what Kierkegaard called “ethical” and “ethical-religious” forms of communication in his unpublished manuscripts.